2021
DOI: 10.3390/biom11020206
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis, Characterization, Enzyme Inhibition, Antimicrobial Potential, and Cytotoxic Activity of Plant Mediated Silver Nanoparticle Using Ricinus communis Leaf and Root Extracts

Abstract: The need of non-toxic synthesis protocols for nanoparticles arises developing interest in biogenic approaches. The present project was focused on cost effective, environment congenial synthesis of Ag nanoparticles and their biological applications. Leaf and root extracts of Ricinus communis were used as a reducing and stabilizing agent in synthesis process. A Proposed mechanism in published literature suggested that Indole-3-acetic acid, l-valine, triethyl citrate, and quercetin-3-0-p-d-glucopyranoside phytoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…Zinc oxide nanoparticles are one of the five zinc compounds that are presently registered and commonly believed as safe by the US Drug and Food Management. These zinc oxide nanoparticles have an antibacterial effect on Gram-positive and Gram-negative bacteria such as Escherichia coli , Pseudomonas aeruginosa , and Staphylococcus aureus [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide nanoparticles are one of the five zinc compounds that are presently registered and commonly believed as safe by the US Drug and Food Management. These zinc oxide nanoparticles have an antibacterial effect on Gram-positive and Gram-negative bacteria such as Escherichia coli , Pseudomonas aeruginosa , and Staphylococcus aureus [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TEM micrographs showed that the AgNPs were spherical and monodispersed, with an average size of 23.7 nm. Similarly, Gul et al [ 50 ] derived AgNPs from Ricinus communis leaf and root extracts as reducing and stabilizing agents, while the TEM results confirmed that the subsequently synthesized particles were subspherical with mean sizes of 29 nm and 38 nm, respectively. Additionally, Padalia et al [ 51 ] synthesized AgNPs by reducing an AgNO 3 aqueous solution with Tagetes erecta flower broth as a reductant.…”
Section: Resultsmentioning
confidence: 81%
“…Barleria acanthoides contains two potent phenolic glycosides called barlerisides A (IC50= 419.0 ± 3.167 µM) and barlerisides B (IC50= 426.7 ± 1.87 µM), but they possessed weak activity against xanthine (Karim et al, 2009) at 100 µg/mL, and Cassia absus 29.2% (n-butanol extract) at 5 mg/mL. Gul et al, (2021) conducted a study on Ricinus communis roots and its leaves methanolic extract, and also prepared their silver nanoparticles. This research suggested that XOI% of the methanolic extract of silver nanoparticles (roots 83.6%, and leaves 83%) showed more effectiveness in comparison to simple methanolic extract (roots 23%, and leaves 24%).…”
Section: Figure 3 Parts Of Medicinal Plants Used In Different Studiesmentioning
confidence: 99%